Crystal Reconstruction of Mo:BiVO4: Improved Charge Transport for Efficient Solar Water Splitting - Jeong, Yoo Jae; Seo, Dong Hyun; Baek, Ji hyun; Kang, Min Je; Kim, Bit Na; Kim, Sung kyu; Zheng, Xiaolin; Cho, In Sun (Advanced Functional Materials, 2022)
A multifaceted Mo:BiVO4 (mf-BVO) photoanode is grown on F-doped-SnO2 substrates via achemical bath deposition, and the crystal reconstruction process of mf-BVO is found to boost the charge transport efficiency significantly for photoelectrochemical (PEC) water splitting. The mf-BVO exhibits columnar grains with an uncommon (121) texture with high-index facets such as (112), (020), (132), and (204). The texture and high-index facets facilitate rapid surface melting and grain fusion during thermal annealing, thus leading to crystal reconstructed micron-sized BVO grains (cr-BVO). The cr-BVO has a photocurrent density ≈50 times larger than that of mf-BVO. The reason is identified as the significantly improved charge transport efficiency resulting from the dopant activation (increased carrier concentration) and bulky grains (fewer defects). Additionally, the cr-BVO exhibits improved photocorrosion resistance compared to the nanoparticle-based BVO. After coating the oxygen evolution catalyst, the photocurrent density of cr-BVO is further increased to 4.4 mA cm−2 for water oxidation reaction at 1.23 V versus the reversible hydrogen electrode, maintaining a high and stable faradaic efficiency of over 88% for 24 h. These results demonstrate that crystal reconstruction is a facile and effective pathway to improve the charge transport efficiency, opening a new avenue for developing efficient photoelectrodes for PEC water splitting.
Keywords: Bath depositions; BiVO 4; Crystal reconstruction; High index facets; Multifaceted; Photo-anodes; Photocurrent density; Photoelectrochemical water splitting; Solar water splitting; Transport efficiency; BiVO 4; charge transport; crystal reconstruction; multifaceted; photoelectrochemical water splitting